Palaeocampa anthrax, an armored freshwater lobopodian with chemical defenses from the Carboniferous - Richard J. Knecht; Christian R. A. McCall; Cheng-Chia Tsai; Richard A. Rabideau Childers; Nanfang Yu (Communications Biology)
Abstract Lobopodians are an evolutionary grade of panarthropods characterized by their vermiform bodies and paired, unjointed lobopodous legs. A paraphyletic group, their study is of particular significance in understanding the evolution of extant panarthropods. Found exclusively in marine deposits from the Paleozoic, the great majority of species come from Cambrian Konservat-Lagerstätten, with only a few representatives known from the Ordovician, Silurian, and Carboniferous. Here we redescribe Palaeocampa anthrax from the Carboniferous Mazon Creek (USA) and Montceau-les-Mines (France) Lagerstätten as a lobopodian. First published in 1865, nearly fifty years before the discovery of the Burgess Shale, Palaeocampa is historically the first discovered lobopod, and its presence at the slightly younger Montceau-les-Mines (Gzhelian), makes this the youngest known fossil ‘xenusiid’ lobopodian species. We present the case that Palaeocampa most likely inhabited a freshwater environment, contesting the view that Paleozoic lobopodians were exclusively marine. Palaeocampa bears biomineralized dorso-lateral and lateral sclerite sets with a unique architecture unseen in other lobopodian sclerites, which may have been capable of secreting defensive chemicals at their tips. Palaeocampa anthrax represents a major evolutionary step in lobopodians, both in environmental adaptations and in defensive abilities.